Effect of cutting interval to productivity and quality of bangun-bangun (Coleus amboinicus L.) as a forage promising commodity - Sajimin .; N.D. Purwantari; E. Sutedi; Oyo . (Jurnal Ilmu Ternak dan Veteriner, 2011)
Coleus amboinicus Lour is one of well known plant and commonly consumed by lactating women in North Sumatera. It is high, in iron and carotene contents. The objective of the research was to study the productivity of C. amboinicus at different cutting intervals. An experiment was carried out in glasshouse as pot trial. Four treatments of cutting interval were 30 days, 40 days, 50 days and 60 days with 10 replications. The treatment was arranged in randomized complete design. Parameters measured were shoot dry matter, and crude protein, Cu, Zn and B contents of leaves, at the beginning, middle and end of the experiment. Result shows that dry matter yield was significantly influenced by cutting interval (P <0.05). The highest shoot dry matter production was obtained at 60 days) cutting interval (34.1 g /plant ) and the lowest at 50 days cutting interval (19.6 g/plant). Similarly, crude protein and Cu, Zn and B content of shoot were also highest at 60 days cutting interval. The shoot dry matter production declined from first cutting to seventh cutting. Crude protein content at 60 days cutting interval was in a range of 12.31-15.59%. Key Words: Coleus amboinicus, Forage Production, Quality Mineral